2020
DOI: 10.1038/s41598-020-76358-x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental tests of bivalve shell shape reveal potential tradeoffs between mechanical and behavioral defenses

Abstract: Bivalves protect themselves from predators using both mechanical and behavioral defenses. While their shells serve as mechanical armor, bivalve shells also enable evasive behaviors such as swimming and burrowing. Therefore, bivalve shell shape is a critical determinant of how successfully an organism can defend against attack. Shape is believed to be related to shell strength with bivalve shell shapes converging on a select few morphologies that correlate with life mode and motility. In this study, mathematica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…Similarly, 3D printing can be used to create a wide range of prey morphologies to study relationships between shell morphology and strength. Johnson (2020) used 3D printing to test potential trade‐offs between bivalve shell shapes that allow burrowing or swimming and shapes associated with less mobility in taxa that rely on the shells as a mechanical defence. Theoretical shell shapes created for this study were generated mathematically, allowing the comparison of theoretical morphologies with those found in nature.…”
Section: Future Directions: 3d Printingmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, 3D printing can be used to create a wide range of prey morphologies to study relationships between shell morphology and strength. Johnson (2020) used 3D printing to test potential trade‐offs between bivalve shell shapes that allow burrowing or swimming and shapes associated with less mobility in taxa that rely on the shells as a mechanical defence. Theoretical shell shapes created for this study were generated mathematically, allowing the comparison of theoretical morphologies with those found in nature.…”
Section: Future Directions: 3d Printingmentioning
confidence: 99%
“…The results demonstrated potential trade‐offs: morphologies that enable escape may be less resistant to shell crushing by vertebrate predators. In addition, the ability to parameterize carefully the tested morphologies revealed that the direction of shell elongation (away from the umbo) affected shell strength (Johnson, 2020).…”
Section: Future Directions: 3d Printingmentioning
confidence: 99%
See 2 more Smart Citations
“…in contours, growth lines, and umbo curvature, which might be responses to environmental stress (Morais et al 2013). Alongside functional trade-offs in resource allocation between shell building and soft-tissue growth, shell sculpture has been revealed as a functional trait for defence through experiments with printed models ( Johnson 2020). The 3D models I created are effective in visualising preliminary qualitative results that imply differences in developmental processes and resource allocation for the production of different anti-scouring shell morphology -shell inflation and shell sculpture (see section:…”
Section: Distribution Of Sculptured Speciesmentioning
confidence: 99%